Aging, free radicals and antioxidants - Eduardo Menéndez-Álvarez (2025)
The article presents aging as a multifactorial, progressive biological process shaped by intersecting theories, with special focus on oxidative stress and free radical involvement. The Free Radical Theory of Aging posits that reactive oxygen species (ROS), produced both endogenously and via environmental exposures, induce cumulative molecular damage to lipids, proteins, and DNA impacting cellular and tissue integrity. This oxidative stress contributes to age-related degenerative diseases such as cancer and Alzheimer’s. Although antioxidants (both endogenous enzymes and exogenous dietary compounds) offer protective mechanisms against ROS, empirical evidence on their efficacy in extending lifespan remains inconclusive, largely due to bioavailability challenges and systemic complexity. The article also addresses mitochondrial dysfunction and genomic instability especially mitochondrial DNA mutations as key contributors to aging, proposing a dynamic interaction between genetic regulation, oxidative insults, and physiological decline. Experimental findings from animal models suggest associations between oxidative damage and aging phenotypes, though not always consistent across species. The authors advocate for a comprehensive approach that integrates molecular, genetic, and environmental perspectives, urging evidence based public health strategies to manage the rising aging population. In sum, aging is characterized as a heterogeneous, irreversible process not reducible to a single cause but rather to a complex network of biological mechanisms.